Trawling in the Mediterranean: An Exploration of Empirical Relations Connecting Fishing Gears, Otterboards and Propulsive Characteristics of Fishing Vessels - Sala, Antonello; Notti, Emilio; Bonanomi, Sara; Pulcinella, Jacopo; Colombelli, Alessandro (Frontiers in Marine Science, 2019)
Fishing pressure is often expressed in terms of a vessels physical attributes, like tonnage and engine power, while a common definition of fishing capacity identifies vessel size as a convenient proxy for the size of the gear used. Nevertheless, these definitions remain arguable, and the refinement of these fishing descriptors is increasingly being considered. A stronger understanding of the relationship between the standard measures of effort and capacity and fishing mortality remains a primary objective, followed by the need to overcome a traditional approach that simply describes effort, capacity and mortality as linearly related, conferring a greater fishing power to larger vessels. In this perspective, the analysis of trawlers’ technical features in relation to the size and power of the vessel might constitute an essential step. This study specifically investigated a collection of trawling gears’ technical specifications collected by CNR-IRBIM, Ancona. The dataset used includes records from several Mediterranean fisheries, and involves three trawling techniques, including single trawling, twin trawling and pair trawling, and diverse trawling gear categories, comprising demersal/bottom 2-panel trawls (OTB2), demersal/bottom 4-panel trawls (OTB4), pelagic 4-panel trawls (PTM4), semi-pelagic 2-panel trawls (OTM2), semi-pelagic 4-panel trawls (OTM4), and a Mediterranean bottom beam trawl (TBB). We analyzed and described the relationships between vessels’ technical features (LOA, towing force, and engine power), some among the main trawl-metrics (headline length, footrope length, trawl length, square width; fishing circle) and the otterboard’s technical features (height, width, and projected area) in an attempt to enhance fishing capacity definition through the inclusion of the fishing gear deployed. Self-organizing maps (SOM) were used to explore the empirical relationships among different parts of the fishing trawl gears, as well as between some of these parts, the otterboard size and the engine power of the vessel.